Skin lesions in oncology palliative care: Observational study (Research, Society and Development, 2021)
Objective: Describe the characteristics of skin lesions of the type pressure lesions, tumor wounds and Kennedy's terminal ulcers that occur in cancer patients in palliative care. Methodology: Observational, cross-sectional and analytical with a quantitative approach. 99 (100%) patients with skin lesions participated: 67 (67.68%) with tumor lesions, 28 (28.28%) with pressure injuries and 4 (4.04%) with Kennedy's terminal ulcers. Patients admitted to four wards and the oncological wounds outpatient clinic at Ophir Loyola Hospital, from May to November 2019, were included. Results: Tumor lesions presented with malignant ulcerative wounds 32 (44.44%), exudate 50 (69.44%), without odor 46 (63.89%), did not present necrosis 42 (58.33%), without bleeding 40 (55.56%), staging 3 (31.94%), location on the face (25%), without using a dressing (33.33%) and frequency of dressing once a day 69 (95.83%). In pressure injuries, the characteristics were exudate 22 (56.41%), no odor 28 (71.79%), necrosis 27 (69.23%), bleeding 32 (82.05%), staging II 17 (43 , 59%), sacred location 25 (64.10%), using hydrocolloid dressing 15 (38.46%) and frequency of dressing once a day (64.10%) and Kennedy's terminal ulcers, exudate 4 ( 66.67%), grade II odor 3 (50%), necrosis 4 (66.67%), bleeding 4 (66.67%), sciatic location 3 (50%), pear shape 3 (50%), using a dressing with chlorhexidine and metronidazole 3 (50%). Conclusion: it was shown the importance of individual assessment according to the needs and demands of each patient to seek comfort and quality of life.